Tissue no-reflow despite full recanalization following thrombectomy for anterior circulation stroke with proximal occlusion: A clinical study. Issue 2 (February 2021) - Schiphorst, Adrien ter; Charron, Sylvain; Hassen, Wagih Ben; Provost, Corentin; Naggara, Olivier; Benzakoun, Joseph; Seners, Pierre; Turc, Guillaume; Baron, Jean-Claude; Oppenheim, Catherine
Despite early thrombectomy, a sizeable fraction of acute stroke patients with large vessel occlusion have poor outcome. The no-reflow phenomenon, i.e. impaired microvascular reperfusion despite complete recanalization, may contribute to such "futile recanalizations". Although well reported in animal models, no-reflow is still poorly characterized in man. From a large prospective thrombectomy database, we included all patients with intracranial proximal occlusion, complete recanalization (modified thrombolysis in cerebral infarction score 2c–3), and availability of both baseline and 24 h follow-up MRI including arterial spin labeling perfusion mapping. No-reflow was operationally defined as i) hypoperfusion ≥40% relative to contralateral homologous region, assessed with both visual (two independent investigators) and automatic image analysis, and ii) infarction on follow-up MRI. Thirty-three patients were eligible (median age: 70 years, NIHSS: 18, and stroke onset-to-recanalization delay: 208 min). The operational criteria were met in one patient only, consistently with the visual and automatic analyses. This patient recanalized 160 min after stroke onset and had excellent functional outcome. In our cohort of patients with complete and stable recanalization following thrombectomy for intracranial proximal occlusion, severe ipsilateral hypoperfusion on follow-up imaging associated with newly developed infarction was a rare occurrence. Thus, no-reflow may be infrequent in human stroke and may not substantially contribute to futile recanalizations.